Systemic estradiol levels with low-dose vaginal estrogens. Issue 3 (March 2020) - Santen, Richard J.; Mirkin, Sebastian; Bernick, Brian; Constantine, Ginger D.
Abstract: Objectives: To critically evaluate published systemic estradiol levels during use of low-dose vaginal estrogens considering detection method and estrogen dose; describe challenges with accurately measuring estradiol; and determine the normal estradiol level range in postmenopausal women. Methods: PubMed was searched for studies reporting systemic estradiol levels with lower-dose vaginal estrogens (⩽25 μg estradiol or 0.3 mg conjugated equine estrogens). Estradiol levels at baseline and during treatment, area under the curve, and maximum estradiol concentrations were summarized by dose within assay type. A proposed range of systemic estradiol in normal, untreated, postmenopausal women was estimated by conservatively pooling means and standard deviations from published studies. Results: Mean basal estradiol levels were 3.1 to 4.9 pg/mL using liquid or gas chromatography/mass spectroscopy (LC or GC/MS/MS) with a range of undetectable to 10.5 pg/mL using radioimmunoassay. Systemic estradiol levels with vaginal estrogens reflected their doses as measured with LC or GC/MS/MS in different studies: 7.1 to 9.1 pg/mL and 16.7 to 22.7 pg/mL with a 25-μg softgel capsule insert and a tablet insert, respectively; 4.6 to 7.4 pg/mL and 6.6 to 14.8 pg/mL with a 10-μg softgel capsule and a tablet insert, respectively; and 3.6 to 3.9 pg/mL with a 4-μg softgel capsule insert. A mean systemic estradiol concentration ranging from undetectable to 10.7 pg/mL is proposed as an estimate for basal estradiol levels in normal, untreated, postmenopausal women. Systemic estradiol absorption may be influenced by the placement of estradiol higher (as with an applicator) versus lower (as without an applicator) in the vagina, as estradiol transport to the uterus would be more likely further away than closer to the introitus. Conclusion: Serum estradiol concentrations were generally lower when measured with more specific and sensitive assays. Estradiol absorption was dose-dependent, and may be influenced by dose, formulation, and positioning in the vagina. Very low systemic estradiol absorption with low/ultralow-dose vaginal estrogens may potentially decrease any adverse events that may be associated with higher doses of vaginal estrogens used for treating moderate to severe VVA due to less estradiol exposure.